Water Separation and Formation of Cells with Differential Aeration as Factors Controlling Corrosion of Steel Pipelines in a Crude Oil Storage Facility - Václav Šefl; Rojina Shrestha; Tomáš Prošek (Metals)
The mechanism causing the dramatic intensification of the corrosion deterioration of carbon steel pipes in a crude oil storage facility has been investigated. This study considers a number of factors affecting corrosion in crude oil, such as the water content, the corrosivity of the aqueous phase, the kinetics of water–oil separation, the effect of dissolved oxygen, the effect of the crude oil quality, the degree of stagnancy inside of the pipes, the possible contribution of microbially induced corrosion (MIC) and the presence of deposits. The key root of the corrosion intensification was the separation of the water phase, supported by stagnancy, which eventually led to the formation of stable shallow pits surrounded by cathodic areas.